Reversed-Phase High-Performance Liquid Chromatographic for Quantifying –IBA-HAP Conjugate in Innovative Transdermal Emulgel Formulations - Angam, Kalyani (Asian Journal of Pharmaceutics (AJP), 2024)
Objectives: This research presents a reversed-phase high-performance liquid chromatographic (RP-HPLC) approach that is easy, precise, accurate, and economical for the quantification off or the estimation of IBA-HAP conjugate (IBA-HAP). The lack of a suitable ultraviolet chromophore makes the conjugate of ibandronate Hydroxyapatite challenging. An important challenge with the absence of a chromophore impacts the process of separation. Materials and Methods: It is challenging to preserve the Ibandronate hydroxyapatite conjugates on traditional reversed-phase columns due to their structural makeup. Separation was achieved by column C–18 (pore size – 5 μm and column dimensions (4.6 × 250 mm). The mobile phase comprises of 0.01 M sodium dihydrogen phosphate (NaH2PO4) and Acetonitrile at a ratio of 75:25 with orthophosphoric acid being used to adjust the pH to 3.5 with a flow rate of 1 mL/min at 35°C column temperature. The analysis was monitored using a photodiode array detector. Results: The results indicated a linear response (R2 = 0.9998) in the range of 0.125 μg/mL-1–6 μg/mL-1. The estimated limits of quantification were determined to be 0.167 μg/mL-1. These techniques were then successfully used to estimate the IBA-HAP content during drug content estimation and in vitro through dialysis membrane 60 and ex vivo studies through Rat skin. Conclusion: the developed approach was precise, robust, sensitive, reliable, and incredibly easy. Retention times are fast and highly sensitive, rendering them suitable for both routine and bioanalysis analyses.